The evaluation of epilepsy and other contributing disorders in patients with cerebral palsy using the Gross Motor Function Classification System - Ekici, Arzu; Carman, Kursat Bora; Yimenicioglu, Sevgi; Kocak, Ozan; Yarar, Coskun; Yakut, Ayten; Arslantas, Didem; Saylisoy, Suzan (The European Research Journal, 2017)
Objectives. Morbidity and mortality in patients with cerebral palsy are related to motor function disability, as well as other contributing disorders. The aim of this study was to evaluate the contribution of epilepsy and other disorders in cerebral palsy patients using the Gross Motor Function Classification System (GMFCS), and to determine their relationship. Methods. This study was performed in Eskişehir Osmangazi University School of Medicine, Department of Pediatric Neurology between May 2011-January 2012, with a total of 154 patients diagnosed with cerebral palsy. Epilepsy and other contributing disorders were evaluated in the patients. GMFCS was used to measure the motor function. Results. Mental retardation (89.6%), ophthalmological problems (68.2%) and epilepsy (61.0%) were the leading disorders, followed by oromotor dysfunction (48.7%), malnutrition (40.9%), orthopedic problems (38.3%), dental problems (18.8%), sleep disorders (17.5%) and hearing loss (9.1%) in cerebral palsy patients. Epilepsy, mental retardation, oromotor dysfunction and malnutrition were mostly observed in GMFCS level 5 (p<0.001). Sleep disorder and dental problems were mostly observed at level 5 (p<0.05). Epilepsy was seen more frequently in patients who had neonatal seizure history, microcephaly and mental retardation (p<0.05). Conclusions. There are correlations between the occurrence of disorders such as mental retardation, epilepsy, oromotor dysfunction, malnutrition, sleep disorders, dental problems and gross motor function levels. GMFCS levels were thought to be instructive for possible additional disorders.